Can fecal calprotectin accurately identify histological activity of ulcerative colitis? A meta-analysis. (February 2021) - Ye, Xiaoqi; Wang, Ying; Wang, Harry H. X.; Feng, Rui; Ye, Ziyin; Han, Jing; Li, Li; Zeng, Zhirong; Chen, Minhu; Zhang, Shenghong
Background and Aims: Elevated fecal calprotectin (FC) levels have been reported to correlate with histological activity in patients with ulcerative colitis (UC). However, the accuracy of FC for evaluating histological activity of UC remains to be determined. The aim of this study was to determine the accuracy of FC for evaluating histological activity of UC, based on updated definitions. Methods: Related studies were retrieved from the PubMed, Web of Science, Embase, and Cochrane databases. Adult participants diagnosed with UC were included when sufficient data could be extracted to calculate the accuracy of FC for evaluating histological activity. The primary outcome was histological response, and the secondary outcome was histological remission, defined according to a recently updated position paper of European Crohn's and Colitis Organization. Statistics were pooled using bivariate mixed-effects models. The area under the curve was estimated by summary receiver-operating characteristic curves. Results: Nine studies were included, from which 1039 patients were included for the analysis of histological response and 591 patients for histological remission. For the evaluation of histological response, the pooled sensitivity, specificity, and the area under the curve were 0.69 [95% confidence interval (CI): 0.52–0.82], 0.77 (95% CI: 0.63–0.87), and 0.80 (95% CI: 0.76–0.83), respectively. For the evaluation of histological remission, the corresponding estimates were 0.76 (95% CI: 0.71–0.81), 0.71 (95% CI: 0.62–0.78), and 0.79 (95% CI: 0.75–0.82), respectively. FC had a higher accuracy in studies using Nancy Index. For histological response, the cut-off values of FC ranged from 50 to 172 µg/g, and the sensitivity was higher in studies with FC cut-off values >100 µg/g (0.77 versus 0.65). Conclusion: FC is a valuable biomarker for assessing histological activity in patients with UC. A cut-off value of 100–200 µg/g is more appropriate to spare patients from an unnecessary endoscopy and biopsy.